Rancangan Sistem Informasi Online Booking pada Salon â€Cantikâ€ - Georgiana, Vina (ComTech: Computer, Mathematics and Engineering Applications, 2011)
A management can utilize information technology to produce effective and efficient business process that eventually will increase customer satisfaction. The purpose of this study is to analyze and design the needs of online booking information system of Cantik Salon. In conducting the analysis and system design, object-oriented method is applied using Mathiassen approach.